A study on retirement planning behaviour among working individuals in Coca-Cola Refreshment Malaysia Sdn.Bhd (CCRM) / Farahieza Suriatie Mohd Rani - Mohd Rani, Farahieza Suriatie (Faculty of Business and Management, 2015)
Behavior of retirement planning has been found to be low among people in Malaysia. Much of past research has revealed that working individuals in Malaysia are less awareness towards retirement planning. This study aims to examine the influence of employees’ income receives employees’ attitude towards retirement and employees’ financial knowledge on retirement planning behavior among Coca-Cola Refreshment Malaysia’s employees. Random sampling technique was applied as the sampling technique and 100 respondents were participated in this study. This study was applied Pearson Correlation analysis to determine the relationship between dependent variables and independent variables. This finding reveals that retirement planning behavior is positively correlated with employees’ attitude towards retirement, employees’ financial knowledge and employees’ income level among Coca-Cola’s employees. This study has concluded that only two demographic variables are significant with employees’ behavior towards retirement which is respondent aging and respondents’ income level. For independent variables, this study found that employees’ income level, employees’ attitude toward retirement and employees’ financial knowledge are significant predictors toward retirement planning behavior. This study is advisable for working individuals in Malaysia to plan for an early retirement planning, thus lead to better financial base during their retirement life.